Body atlas: the brain - Copestake, Timothy (Discovery Health Channel, LLC.)
Are the brain and mind one and the same? Is there a ghost in human machine? The brain details how are nerves relay message around the body and reflexes originate in the lower brain. Learn about how the gray matter of our cerebral cortex thinks. Visits the location centers of sight, hearing and speech, and witness how functions like memory are distributed throughout the brain.
In English.
Summary taken from the container.
Executive producer, Willian Cran; Series producer, Belinda Giles
Keywords: Brain -- Atlasses